Blood neurofilament light as a potential endpoint in Phase 2 studies in MS. Issue 6 (28th May 2019) - Sormani, Maria Pia; Haering, Dieter A.; Kropshofer, Harald; Leppert, David; Kundu, Uma; Barro, Christian; Kappos, Ludwig; Tomic, Davorka; Kuhle, Jens
Abstract: Objectives: To assess whether neurofilament light chain (NfL) could serve as an informative endpoint in Phase 2 studies in patients with relapsing–remitting multiple sclerosis (RRMS) and estimate the sample size requirements with NfL as the primary endpoint. Methods: Using data from the Phase 3 FREEDOMS study, we evaluated correlation of NfL at Month 6 with 2‐year outcomes: relapses, confirmed disability worsening (CDW), new or enlarging T2 lesions (active lesions), and brain volume loss (BVL). We compared the proportion of treatment effect (PTE) on 2‐year relapses and BVL explained by 6‐month log‐transformed NfL levels with the PTE explained by the number of active lesions over 6 months. We estimated sample size requirements for different treatment effects. Results: At Month 6, blood NfL levels (pg/mL, median [range]) were lower in the fingolimod arm (fingolimod ( n  = 132) 18 [8–247]; placebo ( n  = 114) 26 [8–159], P  < 0.001). NfL at 6 months correlated with number of relapses ( r  = 0.25, P  < 0.001), 6‐month CDW (hazard ratio 1.83, P  = 0.012), active lesions ( r  = 0.46, P  < 0.001), and BVL ( r  = −0.41, P  < 0.001) at Month‐24. The PTE (95% CI) on 24‐month relapses and BVL explained by 6‐month NfL was 25% (8–60%) and 60% (32–132%), and by 6‐month active lesions was 28% (11–66%) and 45% (18–115%), respectively. Assuming a 20–40% treatment‐related reduction in NfL levels, 143‐28 patients per arm will be required. Conclusions: Blood NfL may qualify as an informative and easy‐to‐measure endpoint for future Phase 2 clinical studies that captures both inflammatory‐ and noninflammatory‐driven neuroaxonal injury in RRMS.